Development of a suite of IPv6 vulnerability scanning tests using the TTCN-3 language - Leal, Adriano Galindo; Teixeira, Igor Cunha (ISNCC 2018 : the 2018 International Symposium on Networks, Computers and Communications : 19-21 June, 2018, Rome, Italy, 2018)
With the transition from IPv4 IPv6 protocol to improve network communications, there are concerns about devices and applications' security that must be dealt at the beginning of implementation or during its lifecycle. Automate the vulnerability assessment process reduces management overhead, enabling better management of risks and control of the vulnerabilities. Consequently, it reduces the effort needed for each test and it allows the increase of the frequency of application, improving time management to perform all the other complicated tasks necessary to support a secure network. There are several researchers involved in tests of vulnerability in IPv6 networks, exploiting addressing mechanisms, extension headers, fragmentation, tunnelling or dual-stack networks (using both IPv4 and IPv6 at the same time). Most existing tools use the programming languages C, Java, and Python instead of a language designed specifically to create a suite of tests, which reduces maintainability and extensibility of the tests. This paper presents a solution for IPv6 vulnerabilities scan tests, based on attack simulations, combining passive analysis (observing the manifestation of behaviours of the system under test) and an active one (stimulating the system to become symptomatic). Also, it describes a prototype that simulates and detects denial-of-service attacks on the ICMPv6 Protocol from IPv6. Also, a detailed report is created with the identified vulnerability and the possible existing solutions to mitigate such a gap, thus assisting the process of vulnerability management.